Anti‑leishmanial compounds from microbial metabolites: a promising source - Cunha, Ana F. S. da (2021)
Leishmania is a complex disease caused by the protozoan parasites and transmitted by female phlebotomine sandfly. The disease affects some of the poorest people on earth with an estimated 700,000 to 1 million new cases annually. The current treatment for leishmaniasis is toxic, long, and limited, in view of the high resistance rate presented by the parasite, necessitating new perspectives for treatment. The discovery of new compounds with different targets can be a hope to make the treatment more efficient. Microbial metabolites and their structural analogues with enormous scaffold diversity and structural complexity have historically played a key role in drug discovery. We found thirty-nine research articles published between 1999 and 2021 in the scientific database (PubMed, Science Direct) describing microbes and their metabolites with activity against leishmanial parasites which is the focus of this review.